Global Modern Art Europe, the Americas, Asia, and Africa - Richardson, Margaret A. (London Taylor & Francis; Routledge, 2025)
Introduction: The Coming Together of the World: Modern Conditions, Many Modernisms, and Common Themes 1. Modern Models: Modern Art in Europe, ca.1850-1914 2. Balancing Order and Chaos: European Art around the World Wars 3. Internationalism and Isolationism: Modern Identities in the US and Canada 4. Between Internationalism and Indigenism: Modern Art in Latin America 5. Colonial Modernities in South and Southeast Asia and the Pacific 6. Defensive Modernities in Thailand and East Asia 7. Modernitys Complexities in West Asia and North Africa 8. Paradoxical Modernities in Sub-Saharan Africa
E-Book / Zugriff nur im Lesesaal